2000
DOI: 10.1074/jbc.275.10.7280
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the Promoter Region of the Rat Epidermal Growth Factor Receptor Gene and Its Transcriptional Regulation by Nerve Growth Factor in PC12 Cells

Abstract: Our previous studies have shown that treatment of PC12 cells with nerve growth factor (NGF) causes a profound down-regulation of the epidermal growth factor receptor (EGFR) mRNA and protein. Further, the NGFinduced down-regulation of the EGFR is under transcriptional control. To elucidate the molecular mechanism of this down-regulation we have cloned a 2.7-kilobase sequence from the promoter region of the rat EGFR from a rat P1 library. Six transcriptional start sites were identified by 5-rapid amplification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…3, lanes 3 and 4). In support of this result, mutations in TCC repeat sequences abolished the binding of WT1 in electrophoretic mobility shift analysis as described previously (6). Thus, some of complex A contains WT1 that reacts with anti-WT1.…”
Section: Fig 1 Transcriptional Activation Of the Rat Egfr Promoter mentioning
confidence: 50%
See 3 more Smart Citations
“…3, lanes 3 and 4). In support of this result, mutations in TCC repeat sequences abolished the binding of WT1 in electrophoretic mobility shift analysis as described previously (6). Thus, some of complex A contains WT1 that reacts with anti-WT1.…”
Section: Fig 1 Transcriptional Activation Of the Rat Egfr Promoter mentioning
confidence: 50%
“…Activates the Promoter Activity of the Rat EGFR Promoter-Recently, we isolated and characterized the promoter region of the rat EGFR promoter, and we found that TCC repeat sequences in the promoter region are required for NGFinduced transcriptional down-regulation of EGFR (6). The TCC repeat sequences in the human EGFR promoter have been reported to be a DNA-binding sequence for the Wilms' tumor repressor, WT1 (16).…”
Section: Wt1mentioning
confidence: 99%
See 2 more Smart Citations
“…EGFR promoter reporter plasmid (pER-Luc) from Dr Alfred C. Johnson (Liu et al, 2000); Expression constructs for hEGFR and hEGFR (Y1045F) mutant were from Dr Yosef Yarden (Levkowitz et al, 1999); pcDNA3.1-HA-Ubiquitin from Dr De Camilli P; CD19-Fc and EphA2-Fc expression vectors from Dr Hans-Christian Aasheim (Finne et al, 2004).…”
Section: Plasmids Construction and Cell Transfectionmentioning
confidence: 99%